2021
DOI: 10.3390/ijms22115598
|View full text |Cite
|
Sign up to set email alerts
|

Preferent Diaphragmatic Involvement in TK2 Deficiency: An Autopsy Case Study

Abstract: Our goal was to analyze postmortem tissues of an adult patient with late-onset thymidine kinase 2 (TK2) deficiency who died of respiratory failure. Compared with control tissues, we found a low mtDNA content in the patient’s skeletal muscle, liver, kidney, small intestine, and particularly in the diaphragm, whereas heart and brain tissue showed normal mtDNA levels. mtDNA deletions were present in skeletal muscle and diaphragm. All tissues showed a low content of OXPHOS subunits, and this was especially evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Notably, respiratory failure is consistently the cause of mortality in all cases, confirming our previous emphasis on the early and prominent involvement of the diaphragm in this condition. 16 , 28 This aspect is highly relevant for diagnosis and monitoring, even in patients with milder phenotypes, such as those with apparent isolated CPEO. 14 , 18 , 49 Of interest, besides the classical phenotype, this cohort includes 3 patients with isolated exercise intolerance and rhabdomyolysis episodes, one of them previously reported in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, respiratory failure is consistently the cause of mortality in all cases, confirming our previous emphasis on the early and prominent involvement of the diaphragm in this condition. 16 , 28 This aspect is highly relevant for diagnosis and monitoring, even in patients with milder phenotypes, such as those with apparent isolated CPEO. 14 , 18 , 49 Of interest, besides the classical phenotype, this cohort includes 3 patients with isolated exercise intolerance and rhabdomyolysis episodes, one of them previously reported in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Partial clinical data from several patients were previously published elsewhere. 16 , 19 , 21 , 28 - 31 …”
Section: Methodsmentioning
confidence: 99%
“…
Fig. 5 Proposed TK2d diagnostic algorithm [ 9 , 28 , 29 ]. COX, cytochrome C oxidase deficiency; CSUR, National Reference Centers; EMG, electromyography; ENT, ear, nose, and throat; MRI, magnetic resonance imaging; mtDNA, mitochondrial DNA; NIMV, non-invasive mechanical ventilation; TK2d, thymidine kinase 2 deficiency
…”
Section: Main Bodymentioning
confidence: 99%
“…On the other hand, changes in key genes that are associated with the stability of the mtDNA genome are the main endogenous factors that cause mtDNA mutation. It has been demonstrated that numerous genes participate in the generation of mtDNA mutations, such as SLC25A4 ( Finsterer & Zarrouk-Mahjoub, 2018 ), FBXL4 ( Alsina et al, 2020 ), thymidine kinase 2 ( Laine-Menéndez et al, 2021 ) and so on. P53 is an important regulator of normal mitochondrial and cellular physiology, and its aberrant expression affects mitochondrial function, mitochondrial biogenesis, mtDNA abundance and tumor suppressor activity ( Bergeaud et al., 2013 ; Koczor et al., 2012 ; Yadav et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%